.121221222 . . . Is Not Quadratic - Luca, Florian (Revista Matemática Complutense, 2005)
In this note, we show that if b > 1 is an integer, f(X) 2 Q[X] is an integer valued quadratic polynomial and K > 0 is any constant, then the b-adic number(...) where an 2 Z and 1 |an| K for all n 0, is neither rational nor quadratic.